2012
DOI: 10.1007/s00412-012-0363-z
|View full text |Cite
|
Sign up to set email alerts
|

Altered distribution of MLH1 foci is associated with changes in cohesins and chromosome axis compaction in an asynaptic mutant of tomato

Abstract: In most multicellular eukaryotes, synapsis [synaptonemal complex (SC) formation] between pairs of homologous chromosomes during prophase I of meiosis is closely linked with crossing over. Asynaptic mutants in plants have reduced synapsis and increased univalent frequency, often resulting in genetically unbalanced gametes and reduced fertility. Surprisingly, some asynaptic mutants (like as1 in tomato) have wild-type or increased levels of crossing over. To investigate, we examined SC spreads from as1/as1 micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 88 publications
0
12
0
Order By: Relevance
“…A number of studies indicate that axis integrity and continuity are important for regulating crossover rate and interference (Hillers and Villeneuve 2003; Kleckner et al 2004;Nabeshima et al 2004;Novak et al 2008;Storlazzi et al 2008;Tsai et al 2008;Joshi et al 2009;Mets and Meyer 2009;Thacker and Keeney 2009;Zanders and Alani 2009;Qiao et al 2012b;Libuda et al 2013;Murdoch et al 2013;Zhang et al 2014d). These data suggest that homolog axes may be the conduits for transmission of interference signaling, or at least that axis integrity is important for spreading of interference (e.g., Zhang et al 2014d).…”
Section: Crossover Control Crossover Assurance and Interferencementioning
confidence: 98%
See 1 more Smart Citation
“…A number of studies indicate that axis integrity and continuity are important for regulating crossover rate and interference (Hillers and Villeneuve 2003; Kleckner et al 2004;Nabeshima et al 2004;Novak et al 2008;Storlazzi et al 2008;Tsai et al 2008;Joshi et al 2009;Mets and Meyer 2009;Thacker and Keeney 2009;Zanders and Alani 2009;Qiao et al 2012b;Libuda et al 2013;Murdoch et al 2013;Zhang et al 2014d). These data suggest that homolog axes may be the conduits for transmission of interference signaling, or at least that axis integrity is important for spreading of interference (e.g., Zhang et al 2014d).…”
Section: Crossover Control Crossover Assurance and Interferencementioning
confidence: 98%
“…Several studies have established that the metric of crossover interference is the physical lengths of prophase chromosomes (as opposed to genetic distance or genomic distance, i.e., bps of DNA) (Martini et al 2006;Drouaud et al 2007;Petkov et al 2007;Zhang et al 2014b). Thus, crossover rates for the same chromosomes vary coordinately with changes in axis lengths, which reflect differences in chromatin packaging with respect to the size and density of chromatin loops (Lynn et al 2002;Hillers and Villeneuve 2003;Kleckner et al 2003;Tease and Hulten 2004;Qiao et al 2012b;Gruhn et al 2013;Baier et al 2014). For example, in humans, variation in the lengths of prophase chromosomes account for long-known differences in recombination rates between males and females.…”
Section: Crossover Control Crossover Assurance and Interferencementioning
confidence: 99%
“…In line with this hypothesis, we observed that only a small fraction of HEI10 and MLH1 foci colocalized at diakinesis in B. napus allohaploids ( Figure 6F), while this was systematic in euploids ( Figure 4E; Supplemental Figure 9E). The nature of these separate HEI10 and MLH1 foci is unknown, but it is probably no coincidence that they were found in plants showing partial synapsis (Qiao et al, 2012, and references therein). As recently proposed for the tomato (Solanum lycopersicum) asynaptic mutant as1 (Qiao et al, 2012) or haploid Arabidopsis (Cifuentes et al, 2013), the "stand-alone" MLH1 foci could in fact mark the locations where COs eventually failed or occurred between sister chromatids.…”
Section: Variation In Class I Co Numbers Between B Napus Varietiesmentioning
confidence: 99%
“…The nature of these separate HEI10 and MLH1 foci is unknown, but it is probably no coincidence that they were found in plants showing partial synapsis (Qiao et al, 2012, and references therein). As recently proposed for the tomato (Solanum lycopersicum) asynaptic mutant as1 (Qiao et al, 2012) or haploid Arabidopsis (Cifuentes et al, 2013), the "stand-alone" MLH1 foci could in fact mark the locations where COs eventually failed or occurred between sister chromatids. As there is bias against forming COs between sister chromatids (at least in haploid Arabidopsis; Cifuentes et al, 2013), it is possible that a fraction of late recombination intermediates are still in the process of being resolved at diakinesis in B. napus allohaploids, resulting in some HEI10 foci persisting longer than usual on chromosomes without producing the conditions required for MLH1 loading.…”
Section: Variation In Class I Co Numbers Between B Napus Varietiesmentioning
confidence: 99%
“…Meiotic sister chromatid cohesion (SCC) is needed for both the proper alignment of chromosomes at the metaphase plate and to create tension across the centromeres, which counteracts the pull of microtubules to allow for correct monopolar attachment to the spindle during anaphase I [Wassmann, 2013]. In addition, cohesins have been implicated in determining the meiotic chromosome structure that is required for proper chromosome pairing and recombination [Golubovskaya et al, 2006;Qiao et al, 2012]. In prophase I of meiosis, plant cohesins are present at the centromeres as well as over the length of the chromosome arms [Lam et al, 2005;Golubovskaya et al, 2006;Wang et al, 2009;Qiao et al, 2011;Shao et al, 2011].…”
Section: Cohesinsmentioning
confidence: 99%